2017
DOI: 10.1002/ange.201708276
|View full text |Cite
|
Sign up to set email alerts
|

A Radiolabeling‐Free, qPCR‐Based Method for Locus‐Specific Pseudouridine Detection

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Because loss of PUS4 did not phenocopy [ BIG + ] but did block propagation of the prion, we wondered whether the catalytic activity of Pus4 was maintained in [ BIG + ] cells. To measure pseudouridylation in naïve and [ BIG + ] cells, we employed a qPCR-based method that capitalizes on the enhanced susceptibility of pseudouridine to reacting with CMC (1- c yclohexyl-(2- m orpholinoethyl) c arbodiimide metho-p-toluene sulfonate); Figure 5A ; Lei and Yi, 2017 . When pseudouridines are ‘labeled’ by CMC, and these RNAs are used as templates for replication by reverse transcriptase, the enzyme generates nucleotide deletions and other mutations at CMC-labeled sites that can be detected by differences in the melting temperature of the derived nucleic acid duplexes (as compared to non-pseudouridylated or unlabeled controls).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because loss of PUS4 did not phenocopy [ BIG + ] but did block propagation of the prion, we wondered whether the catalytic activity of Pus4 was maintained in [ BIG + ] cells. To measure pseudouridylation in naïve and [ BIG + ] cells, we employed a qPCR-based method that capitalizes on the enhanced susceptibility of pseudouridine to reacting with CMC (1- c yclohexyl-(2- m orpholinoethyl) c arbodiimide metho-p-toluene sulfonate); Figure 5A ; Lei and Yi, 2017 . When pseudouridines are ‘labeled’ by CMC, and these RNAs are used as templates for replication by reverse transcriptase, the enzyme generates nucleotide deletions and other mutations at CMC-labeled sites that can be detected by differences in the melting temperature of the derived nucleic acid duplexes (as compared to non-pseudouridylated or unlabeled controls).…”
Section: Resultsmentioning
confidence: 99%
“… ( A ) Radiolabeling-free, qPCR-based method for locus-specific pseudouridine detection. Illustration is adapted from Scheme 1 of Lei and Yi, 2017 . ( B ) High-resolution melting curve analysis demonstrates that Pus4-dependent pseudouridylation of tRNA AGC (Ala) is maintained in [ BIG + ] cells but not in cells that do not contain Pus4p.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies involving high-throughput sequencing methods and transcriptome mapping revealed the abundance of pseudouridine as an epigenetic modification, i.e. in mRNA as well as in long noncoding RNA (lncRNA) [10][11][12][13][14] . Several experimental and theoretical studies suggest the important contribution of pseudouridine to the structure, dynamics and thermal stability of RNA [15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%